Increased circulating galectin-1 levels are associated with the progression of kidney function decline in patients undergoing coronary angiography - Kuo, Chin-Sung (Sci Rep, 2020)
Galectin-1 modulates acute and chronic inflammation, and is associated with glucose homeostasis and chronic renal disease. Whether the serum galectin-1 level can predict short-term and long-term renal outcomes after contrast exposure in patients undergoing coronary angiography (CAG) remains uncertain. This study aimed to evaluate the relationship between the serum galectin-1 level and the incidence of contrast-induced nephropathy (CIN), and to investigate the predictive role of the circulating galectin-1 level for renal function decline in patients undergoing CAG. In total, 798 patients who had undergone CAG were enrolled. Baseline creatinine and serum galectin-1 levels were determined before CAG. CIN was defined as an increase in the serum creatinine level of 0.5 mg/dl or a 25% increase from baseline within 48 h after the procedure, and renal function decline was defined as > 30% reduction of the estimated glomerular filtration rate from baseline. All patients were followed for at least 1 year or until the occurrence of death after CAG. Overall, CIN occurred in 41 (5.1%) patients. During a median follow-up period of 1.4 ± 1.1 years, 80 (10.0%) cases showed subsequent renal function decline. After adjustment for demographic characteristics, kidney function, traditional risk factors, and medications, higher galectin-1 levels were found to be associated independently with a greater risk of renal function decline [tertile 2: hazard ratio (HR) 5.56, 95% confidence interval (CI) 1.79–17.22; tertile 3: HR 5.56, 95% CI 1.97–16.32], but not with CIN, regardless of the presence of diabetes. In conclusion, higher baseline serum galectin-1 levels were associated with a greater risk of renal function decline in patients undergoing CAG, but were not associated independently with CIN.